Effect of cathode pulse square-wave on the microstructure and corrosion resistance of PEO coatings of AZ91D magnesium alloy prepared in the Na2C4H4O6–KF–Na2SiO3 system. (3rd October 2022) - Meng, Lingfei; Zhang, Wei; Zhang, Song; Zhang, Jifu; Zhang, Chunhua; Ye, Yun; Bao, Zebin; Wang, Fuhui
ABSTRACT: Plasma electrolytic oxidation coatings were formed in Na2 C4 H4 O6 –KF–Na2 SiO3 system on AZ91D magnesium alloy by controlling the single-pulse square-wave and bipolar pulse square-wave, respectively. Potentiodynamic polarisation (PD), electrochemical impedance spectroscopy (EIS) and electrochemical noise measurement (EN) were employed to investigate their corrosion behaviour in 3.5% NaCl solution. The results show that with bipolar pulse mode for PEO process, the growth rate of PEO coating on magnesium alloy first decreased and some micropores were present inside the PEO coating. With the increasing oxidation time, the PEO coating became much homogeneous and the porosity of the coating decreased largely, and the corrosion resistance of PEO coating was enhanced. The use of the bipolar pulse mode is beneficial to the improvement of the compactness and corrision performance of magnesium alloy with PEO treatment for the higher voltage stage and longer oxidation time.